National Imaginary and the Catholic Church: Queer Migrant Women’s Experiences of Exclusionary Moments - Sólveigar- og Guðmundsdóttir, Linda (Social and Health Sciences)
In this article, I discuss the imagined boundaries of belonging in Iceland, the political projects of national identity and religion, and the ways in which those projects affect the everyday social formations for LBTQ+ migrant women. I highlight the interlocutors’ experiences of exclusion, foregrounding resistance and resilience in facing unequal power relations, including racism, sexism, heterosexism and cisgenderism. In the article, I apply theories of critical race, postcolonialism, queer-of-colour critique, queer theology, the relationality of space and place, as well as the politics of belonging and a sense of belonging. I draw on feminist writings concerning queer migrations, intersectionality and assemblage, to analyse interlocutors’ multilayered experiences within the Icelandic context, other cultural frames of reference, and transnationally. I analyse semi-structured interviews with 28 interlocutors, who identify as LBTQ+ migrant women, demigirl, gender queer and non-binary. Six interlocutors are racialised as black or brown, 22 as white, hailing from the Global South and Global North. Two themes were carved out of the analysis, relating to the genealogy and aesthetics of racialisation and othering in Iceland, and experiences of exclusion and resistance within the Catholic Church. In line with the analysis, I advocate for dismantling social hierarchies and exclusionary power structures by foregrounding structural violence and microagressions against disenfranchised groups of individuals in addition to highlighting queer worldmaking practices.